2012
DOI: 10.12816/0002244
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Orientation on the Organizational Performance : A Study on the Islamic Banks in Yemen Using the Partial Least Squares Approach

Abstract: This study used the partial least squares (PLS) approach to examine the effect of entrepreneurial orientation on the organizational performance of the Islamic banks in Yemen. The data for this study were collected from the Yemeni banking sector employing the responses obtained from the branch managers. Out of 56 distributed questionnaires to the Islamic banks' branches, 44 usable questionnaires were returned. Before examining the effect of entreprenurial orientation (EO) on the organizational performance of Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
5
14
0
Order By: Relevance
“…This approves hypothesis 2 under justification from previous works of Mahmood & Hanafi, (2013), Dada & Watson, (2013), Tang & Tang, (2012), Al-Swidi & Al-Hosam, (2012, Campos & Valenzuela, (2013), ISSN 2157-6068 2018, Vol. 9, No.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performancesupporting
confidence: 88%
“…This approves hypothesis 2 under justification from previous works of Mahmood & Hanafi, (2013), Dada & Watson, (2013), Tang & Tang, (2012), Al-Swidi & Al-Hosam, (2012, Campos & Valenzuela, (2013), ISSN 2157-6068 2018, Vol. 9, No.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performancesupporting
confidence: 88%
“…Another study on EO and innovation performance reported a direct and indirect effect of EO on performance (Zainol et al, 2011). Entrepreneurial processes may lead to favorable outcomes on firm performance, EO enhances a firm's ability to take risks, be more innovative and act ahead of competitors (Al-Swidi & Al-Hosam, 2012). Some studies have revealed that EO dimensions are significantly and positively related to business performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, studies have suggested further investigation on the relationship (Macaes et al, 2007). More importantly, past studies have also indicated and recommended for further investigation on this relationship in the banking sector (Al Swidi & Al Hosam, 2012;Mahmood & Wahid, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%